STUDENTS’ PERCEPTION OF THE ENGLISH DAY PROGRAM AT SMA IT AL-HUSNA PEKANBARU - Anggraini, Nesi; Daud, Afrianto; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: English is an international language that is widely used in today's globalized world as a means of communication. In Indonesia, English is used in every formal education setting, from elementary school to university. However, it can be challenging for language learners to practice their English in a natural environment because most of students spend very little time in class and only sometimes practice their English. Therefore, it needs some efforts to help students communicate and use English in daily activities, and one of the alternative ways is called English Day Program. This study aims to find out the students’ perceptions of the English Day Program in improving students’ English skills. The quantitative data collected by the questionnaire and the qualitative data obtained from the interview were analysed employing the descriptive analysis technique. The sample of this research is the secondgrade students of SMA IT Al-Husna Pekanbaru. The results showed that students have a positive perception of the English Day Program in terms of improving their English skills because the overall percentage of agreement levels was higher than the disagreement levels, as well as considering the positive responses from the interview sessions were higher than the negative responses. Keywords: Perception, English Day Program, English Skills